China's Foreign Policies Today Who is in Charge of What - Berkofsky, Axel (ISPI Publications, 2022)
Since Xi Jinping took power in 2012, China's foreign policy has significantly shifted from a defensive to an assertive approach. For decades, Beijing worked to integrate into the liberal international order, presenting itself as a peacefully rising power. By contrast, however, under Xi's leadership, the country is attempting to create a global system that is more favourable to its own interests. The Report examines China's current foreign policy approach, and the drivers behind the country's shift away from tradition. What are the main features of China's foreign policy today? How are decisions being taken, and to what extent do interest groups continue to have a say in decision-making after the recent power centralisation?